Complexes and salts of the nitrogen-rich triazole–tetrazole hybrid ligand with alkali and alkaline earth metal cations: experimental and theoretical findings. (14th June 2017) - Safin, Damir A.; Railliet, Antoine P.; Robeyns, Koen; Mitoraj, Mariusz P.; Kubisiak, Piotr; Sagan, Filip; Garcia, Yann
Abstract : A series of the triazole–tetrazole based compounds with Li +, Na +, K +, Mg 2+, Ca 2+ and Ba 2+ was obtained and fully characterised. Abstract : Reaction of the nitrogen-rich triazole–tetrazole hybrid ligand 5-(4 H -1, 2, 4-triazol-yl)-2 H -tetrazole (trz–tetH ) with Li +, Na +, K + and Ba 2+ in water leads to the coordination polymers[Li(trz–tet)H2 O] n, [Na(trz–tet)(H2 O)2 ] n, [K(trz–tetH)(trz–tet)(H2 O)2 ] n and[Ba2 (trz–tet)4 (H2 O)9 ] n, exhibiting different topologies and coordination modes. Salt-like structures with anionic triazole–tetrazole building blocks[Mg(H2 O)6 ](trz–tet)2 and[Ca(H2 O)8 ](trz–tet)2 were also obtained. All structures were simplified by topological analysis, which showed that the structures of[Mg(H2 O)6 ](trz–tet)2 and[Ca(H2 O)8 ](trz–tet)2 can be considered as underlying networks, constructed from the hydrogen bonded[Mg(H2 O)6 ] 2+ or[Ca(H2 O)8 ] 2+ cations andtrz–tet ligands, with the rare binodal 5, 10-connected topologyalb-5, 10, P21/c-1 and a unique binodal 5, 12-connected topology, respectively. According to TGA/DTA analysis, all compounds show endothermic mass losses below 200 °C due to dehydration processes. The dehydrated residues are stable up to 300 °C. It was also established that the anionic form of the coordinated ligandtrz–tet decomposes with an abrupt mass loss accompanied by a sharp and intense exothermic effect, while the non-coordinatedtrz–tet, as in the structures of the Mg- and Ca-based compounds, decomposes with a more gradual mass loss and significantly broad exothermic effect. Static DFT, ab initio molecular dynamics simulations as well as charge and energy decomposition (ETS-NOCV) based studies are performed in order to shed light on the stability of the newly obtained crystals.